A Study on Molecular Diagnosis of Theileria Species Infection by PCR Amplification in Sheep and Goats in Multan, Pakistan - Riaz, Muhammad; Tasawar, Zahida (Biological Sciences - PJSIR, 2017)
In this present study polymerase chain reaction (PCR) assay was used for identification and differentiation of Theileria species infection in Multan, Pakistan. Out of 220 blood samples collected from sheep and goats, 31.2% (70/220) were found positive for Theileria species by PCR amplification compared to only 9.1% (20/220) on blood smear. Theileria infection was observed in 39.3% (57/145) of sheep and 18.6% (13/75) of goats sampled. The prevalence of Theileria ovis and Theileria lestoquardi in the 70 positive samples was found to be 57% (40/70) and 30% (21/70), respectively with only 12.3% (9/70) of blood samples having a mixed infection of both T. ovis and T. lestoquardi. Overall the prevalence of T. ovis infection was higher than T. lestoquardi in both sheep and goats. Herds with sheep only had significantly higher parasitic prevalence. The results confirm that PCR is direct, specific and sensitive tool for diagnosis of ovine theileriosis.